Elyssa Evans: capstone - Evans, Elyssa, artist and filmmaker (Colorado State University. Libraries, 2017)
The artist's statement: A prominent theme of my work is the blending of different eras, of old and of new, of retro and modern, in aesthetics or in methods of creation. Digital art and design, while a relatively new and modern form of art making, has already had a robust history and quick evolution from primitive shapes to highly detailed rendering. By calling upon different elements and modes of creation from this history, while also drawing influence from modern design and artists, I can create works that both honor and recognize the history of digital art making and create my own unique body of work. My work is also influenced by travel, language and culture, as related to my study of different languages and cultures, and my experience traveling to different countries. These new experiences allow me a unique perspective on issues, modes of creation and aesthetics, because I can draw on a variety of viewpoints and opinions I have been exposed to via these experiences. My work is influenced by artists whose works feature bright colors, a graphic style of illustration, and busy and full compositions. One such artist is Takashi Murakami, whose vibrant color schemes and character's reminiscent of retro cartoons or games inspire the bold colors and retro illustration style I often use in my own work. Another artist I draw influence from is Tomokazu Matsuyama. His paintings also feature bold colors, and the flat, graphical way he is able to lay together the different patterns and effects within his art have influenced the way I organize my own compositions. Creating digital artwork and design in the modern age involves constant innovation. Often this innovation comes from new technology and software, while other times it comes from new ways to manipulate existing software or new ways to display digital artwork. My own work is innovative by utilizing cutting-edge technology, such as VR, and displaying retro styles like pixel art animation in a modern way, like on an iPad or via a modern in-browser game. This combination of aesthetics gives my work a timeless feeling and positive outlook towards digital art's future.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
Video has no spoken word.
Keywords: electronic art; video